COMP-16. CORRELATING MGMT PROTEIN LEVEL WITH TEMOZOLOMIDE RESPONSE IN GLIOBLASTOMA PATIENTS USING MASS SPECTROMETRY. (5th November 2018) - Yan, Dongyao; Schaff, Lauren; Cecchi, Fabiola; Benz, Steve; Rosenblum, Marc; Hembrough, Todd; Lin, Andrew
Abstract: Glioblastoma (GBM) is an aggressive primary brain tumor with median progression-free survival (PFS) of 7 months and median overall survival (OS) of 15 months. Standard treatment at diagnosis consists of surgery, radiation and temozolomide (TMZ). O-6-methylguanine DNA methyltransferase (MGMT) modulates TMZ effect and MGMT promoter methylation status is used to predict outcomes and guide treatment decisions. However, standard testing is limited by poor inter-assay reproducibility and a weak correlation between methylation status and MGMT expression. We quantitated MGMT protein by mass spectrometry in 32 GBM patients to assess its relationship to PFS and OS after upfront TMZ treatment. We obtained archived tumor samples from newly diagnosed GBM patients prior to treatment with surgery, radiation and TMZ. Tumor cells were microdissected and solubilized, and MGMT protein was quantitated using mass spectrometry. PFS (determined by RANO) and OS were assessed using the Kaplan-Meier method and log-rank test. Of the 32 patients (66% male; median age: 63 years), 15 expressed MGMT protein. While methylation status agreed with absence of MGMT protein in 8/9 cases, 9/23 samples with unmethylated MGMT had undetectable MGMT protein, indicating poor agreement between methylation status and protein expression. Patients with MGMT levels below 150 amol/ug of total protein had longer PFS than those with higher MGMT levels (HR: 0.51; p=0.0399; median PFS: 303 vs. 260 days). Similarly, MGMT level below 150 amol/ug was associated with longer OS (HR: 0.49; p=0.0311; median OS: 659 vs. 534 days). Discordance between MGMT methylation status and protein expression was found in 31% of GBM samples. MGMT protein expression below 150 amol/ug correlated with longer PFS and OS in TMZ-treated patients. Mass spectrometry-based MGMT quantitation provides a direct readout of protein expression and may be more reliable than methylation testing.